The Correlation between Self-control and Game online Addiction among students enrolled at State High School 5 (SMA Negeri 5) Samarinda Hubungan Pengendalian Diri dengan Kecanduan Game Online pada Siswa SMA Negeri 5 Samarinda: The Correlation between Self-control and Game online Addiction among students enrolled at State High School 5 (SMA Negeri 5) Samarinda - Sadlina, Radifan Ahmad; Khotimah, Siti; Wibowo, Hutomo Judhi Cristanto (ITKES Wiyata Husada Samarinda, 2024)
Online game addiction refers to a recurring behavioral pattern that is distinguished by a lack of Self-control resulting from excessive engagement in online gaming activities. The growing emphasis on gaming in substitute of daily interests and activities is progressively expanding and enduring, exerting influence on many facets of life. Self-control encompasses the regulation of an individual's physiological, psychological, and behavioral processes through a sequence of self- directed mechanisms. The objective of this study is to investigate the correlation between self-control and online game addiction among students enrolled at SMA Negeri 5 Samarinda. The study used a cross-sectional research approach. The data utilized in this research were obtained via questionnaires that were duly completed by students enrolled at SMA Negeri 5 Samarinda. The sample technique employed in this investigation was the consecutive sampling method. The study's sample size included 87 students. The findings of the analysis reveal a statistically significant p-value of p = 0.000, suggesting a correlation between self-control and online game addiction among adolescents, as indicated by a correlation coefficient of -0.444. The findings of this study indicate a significant association between self-control and online game addiction, characterized by a moderate level of connection between these two variables.Keywords: Self-control, Online game addiction